Delivery Mode Affects Intestinal Microbial Composition and the Development of Intestinal Epithelial Cells - Lyu, Linzheng; Zhou, Xiaohong; Zhang, Meng; Liu, Li; Niu, Haiyue; Zhang, Jiliang; Chen, Shiwei; Gong, Pimin; Jiang, Shilong; Pan, Jiancun; Li, Yuanyuan; Han, Xue; et al. (Frontiers in Microbiology, 2021)
Background: The infant’s intestine contains diverse microbiota, which play an important role in an infant’s health. Objective: This study aimed to analyse the different intestinal microbiota and their function in two delivery modes [vaginal delivery and caesarean section (C-section)] and to investigate the proprieties of bacteria associated with vaginal delivery on the development of intestinal epithelial cells in rat pups. Materials and methods: We evaluated the intestinal microbial diversity of the stool samples of 51 infants of subjects who underwent vaginal delivery and C-section by sequencing the V4 regions of the 16S rRNA gene and predicted the function of the microbiotas. The infant stool microbiota in the vaginal delivery group was associated with the digestive system and cell growth and death, whereas that of the C-section group was associated with membrane transport. Then, we isolated the strains based on function prediction. Results: A total of 95 strains were isolated in the vaginal delivery group. Bifidobacterium bifidum FL-228.1 (FL-228.1) was screened and selected owing to its good surface hydrophobicity, bacterial survivability in the simulated gastrointestinal condition and adhesion ability to the IEC-6 cell line as well as owing to the development of intestinal epithelial cells. Furthermore, in vivo experiments revealed that FL-228.1 exhibited favourable effects on the development of intestinal epithelial cells in rat pups. Conclusions: The results of this study indicate an apparent difference in the bacterial composition of the stool samples collected from infants of the two delivery modes. By analysing and screening the bacteria in infant stool samples, we found that one strain, i.e. B bifidum FL-228.1, exhibited favourable effects on the development of intestinal epithelial cells.